A Rare Case of Peripheral Giant Cell Granuloma associated with Odontome (International Journal of Food and Nutritional Sciences, 2022)
Peripheral giant cell granuloma (PGCG) is a benign tumor of the oral mucosa. Although its etiology is not clear, it may be a consequence of local chronic irritation or persistent trauma. A complex odontoma is a hamartomatous lesion in which all the dental tissues are well formed but occurring in a more or less disorderly pattern. The complex type of an odontome is slow growing and expanding lesions that is usually detected in the second decade of life. A 34 years-old man presented a exophytic growth which was violet-colored with pedunculated base in the buccal aspect of the maxillary left posterior region. Radiographically, the internal structure appeared as a mixed hypodense and hyperdense. Its effect on the adjacent structures included displacement of 28 distally, loss of buccal cortical plate i.r.t 27, 28.